PENGARUH DISSATISFACTION, LOW-QUALITY, DAN ALTERNATIVE ATTRACTIVENESS TERHADAP NIAT BERALIH KONSUMEN KE PRODUK KOSMETIK RAMAH LINGKUNGAN (THE BODY SHOP BRAND) YANG DIMODERASI SWITCHING COST - Marsella, Marsella; Tyra, Maria Josephine; Lina, Lina (LPPM Universitas Multi Data Palembang, 2024)
This study aims to determine the effect of dissatisfaction, low quality, and alternative attractiveness on consumer switching intentions to environmentally friendly cosmetic products moderated by switching costs. The data used is primary data. The sampling technique used was purposive sampling and obtained 198 respondents. The results show that the main factors that influence consumer intention to switch are alternative attractiveness variables and switching costs. While no significant relationship was found between the variables of dissatisfaction, low quality, and the moderating effect of switching costs on these three variables in influencing consumer intention to switch to environmentally friendly cosmetic products.